TOLL-LIKE RECEPTOR 7 GENE Gln11Leu MISSENSEMUTATION AND SUSCEPTIBILITY TO PSORIASIS - E. S. Galimova; K. Kingo; S. Koks (Медицинская иммунология, 2017)
Toll-like receptor (TLR) are responsible for recognizing various molecular patterns associated with pathogens. Their expression have been detected in skin cells such as keratinocytes and melanocytes. Numerous experimental studies demonstrate the key role of TLRs in the pathogenesis of immune diseases, including psoriasis. The objective of this study is to analyze the associations of polymorphisms in TLR7 gene and the risk of psoriasis development. DNA samples were collected from 138 patients with psoriasis and 317 healthy controls. Genotyping of rs179003, rs179008, rs179020, rs850632, rs12013728 polymorphic loci in TLR7 gene was performed using the SNPlex™method (AB, USA). SNP in the TLR7 gene rs179008 (Gln11Leu) was associated with psoriasis in entire psoriasis, late onset and sporadic subgroups (Рс = 0.0065, OR = 1.95; Рс = 0.0004, OR = 2.50; Рс = 0.0078, OR = 2.2, respectively). In conclusion, this study is the first to identify genetic variants of the TLR7 gene significantly associated with psoriasis.